Activated carbon sheets from pomegranate peel with ionic liquid for Knoevenagel condensation: synthesis of aryledene and xanthene derivatives - Prasad, Dhaneshwar; Asatkar, Archana; Ram, Swetlana Prerna; Singh, Shripal; Prajapati, Santosh Kumar; Banerjee, Subhash (Frontiers in Catalysis, 2026)
IntroductionDevelopment of a mild and sustainable protocol for the carbon-carbon bond formation via Knoevenagel condensation is essentially desirable because the products, aryledene derivatives, are useful intermediates and are widely used in the manufacture of fine chemicals, pharmaceutically active molecules, calcium channel blockers, natural products, as well as in the production of flavours and fragrances.MethodActivated carbon sheets were fabricated from pomegranate peels via calcination, activation by KOH and were characterization using Raman spectroscopy, powder XRD, FESEM, FESEM-EDX, and TGA studies. The ionic liquid, [pmIm]Br was synthesized by reacting a 1:1 mixture of N-methyl imidazole and n-pentyl bromide under microwave irradiation.Results and discussionPomegranate peel–derived two-dimensional graphitic activated carbon (PPAC) nanosheets, with lateral dimensions of 40–200 nm and lengths of 4–10 μm, were confirmed through Raman spectroscopy, powder XRD, FESEM, and other studies. The PPAC, combined with the ionic liquid [pmIm]Br, demonstrated remarkable catalytic performance in the Knoevenagel condensation of aromatic aldehydes with active methylene compounds, producing the corresponding aryledene derivatives in excellent yields (90%–95%) within 5–20 minutes under mild conditions. Furthermore, the PPAC/[pmIm]Br catalytic system efficiently facilitated the synthesis of xanthene derivatives via a tandem condensation–cyclization pathway. The catalyst was easily recovered and reused over five consecutive cycles with minimal loss of activity. This work highlights a renewable, biomass-derived carbon framework as a dual-function, environmentally friendly catalyst for effective C–C bond formation and heterocycle synthesis, offering a scalable approach aligned with green chemistry and waste valorization principles.